Перспективи використання smart-антен в мережах мобільного зв’язку 5G - Андрущенко, О. В.; Шумков, І. М. (ХНУРЕ, 2023)
This work is devoted to the assessment of the perspective of using Smart antennas in 5G networks. The advantages of using smart antennas are given. Technologies used in Smart-antennas are listed in the article. The synthesis of a Smart antenna in the form of a linear uniform antenna array is developed. The methods of adaptive formation of the directional pattern of the Smart antenna, namely the least mean squares (LMS) method and recursive least squares (RLS) algorithm, which are used to calculate the weight coefficients of the linear antenna array, are analyzed.